The Dynamics of Social Justice within the Framework of Constitutional Law: Synergy of Agrarian Policy, Environmental Protection, Human Rights, and Bureaucratic Integrity in the Digital Era - Si Yusuf Al Hafiz; Eko Tjahjono; Elmi Sasmitaningtyas; Gasper Doroh; Indra Rukmono (International Journal of Sustainable Law, 2026)
This article comprehensively examines the role of the state in realizing social justice through the harmonization of law and public policy in Indonesia. The main focus of this research is on agrarian policy, specifically examining the problems of absentee land ownership (guntai) which clashes with the social, economic, and bureaucratic realities of the State Civil Apparatus (ASN). Through a juridical-normative and comparative approach, this article explores the effectiveness of the Complete Systematic Land Registration (PTSL) program and a review of Islamic law (Maslahah Mursalah and Maqashid Syariah) in responding to agrarian inequality. The analysis is then expanded across themes by examining the negligence of bureaucratic governance following the abolition of the State Civil Apparatus Commission (KASN) ahead of the 2024 Regional Elections. As a conceptual bridge, this research also integrates the issue of protecting vulnerable groups within the framework of the Sexual Violence Crime Law (TPKS), as well as the ecological dilemma resulting from resource exploitation (nickel downstreaming and the implementation of PLTSa to reduce carbon emissions). This paper concludes that substantive justice can only be achieved if the state is able to eliminate discriminatory regulations, tighten bureaucratic oversight, prioritize human rights, and adopt precise technological integration (such as Artificial Intelligence in maritime governance and land registration).